Stage Wise Presentation of Breast Cancer in Patients Aged Less Than 40 Years Verses Age Above 40 Years - Maryam Munir, Sara Riaz, Sana Sahar, Muhammad Amin, Munazza Ayub, Muhammad Yasir Jan, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Worldwide most common malignancy in females is breast carcinoma and accounts for almost one-third of all women cancers. In developing countries of Asia like in Pakistan, breast carcinoma has the highest incidence. With an age-standardised incidence rate (ASR) of 51.7, and the rate of the new cases of breast cancer is on the rise similar to the Western population. Objectives: The main objective of the study is to analyse the stage wise presentation of breast carcinoma in patients aged <40 years verses age >40 years. Material and methods: This cross sectional study was conducted in Khyber teaching Hospital Peshawar from 2017 to 2020. The data was collected from 200 female patients who were suffering from breast cancer at different stages. The data was collected through a systematically prepared questionnaire after taking consent. Results: The data was collected from 200 female breast cancer patients. Out of which 68 patients were < 40 years and 132 patients were >40 years of age. Majority of patients 90 presented in 41—50 years, followed by 50 cases in 51—60 years and least cases observed in 21—30 years of age. Stage III was the commonest stage in younger patients followed by stage II while in older patients stage ii was common than stage iii. 82 patients presented in stage iii while 70 patients in stage ii. Least cases presented in stage i. 82 patients out of 200 patients presented with stage iii. Overall ductal carcinoma is the most common type of breast carcinoma. Left breast carcinoma is more than right breast carcinoma. Conclusion: It is concluded that breast cancer is more common in older age as compared to young age. In young patients stage iii is more common than stage ii while in old patient’s stage ii is more than stage iii, however overall stage iii has the highest frequency. Keywords: Breast, Cancer, TNM, Factors, Patients